Fabricated concrete pavement material and preparation method thereof
By using POM fiber, PP fiber and limestone calcined clay cement in concrete pavement, combined with electrochemical treatment, the problems of concrete cracking and chloride ion erosion are solved, the toughness and anti-chlorine ion penetration performance are improved, and the cost and carbon emissions are reduced. , suitable for concrete pavement in coastal areas.
Patent Information
- Application Number
- CN202411234399.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2025-01-07
AI Technical Summary
The existing concrete pavement is prone to cracking and poor ductility under repeated vehicle loads and environment action, and the concrete pavement in coastal areas is susceptible to chloride ions, resulting in a shortened service life, high cost of preparation of high-strength and high-tough concrete and high-carbon emissions.
POM fiber and PP fiber are used to replace PVA fiber, limestone calcined clay cement is used to replace silicate cement, and combined with electrochemical methods, the toughness and anti-chlorine ion penetration properties of concrete are improved, and the preparation cost and carbon content are reduced.
It effectively improves the toughness and anti-chlorine ion penetration properties of concrete, reduces preparation costs and carbon emissions, extends the service life of concrete pavement, and is suitable for strong corrosion environments in coastal areas.
Smart Images

Figure CN119263708A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of concrete materials, and in particular relates to an assembled concrete pavement material and a preparation method thereof. Background Art
[0002] Cement concrete pavement has become the most common and widespread rigid pavement form in my country due to its advantages of high strength, good stability and low cost. However, as traffic volume increases, speeding and overloading on the road are becoming more and more common, causing serious damage to the existing concrete pavement structure and a sharp reduction in its service life. Concrete has shortcomings such as easy cracking, poor ductility and low tensile strength. Under repeated vehicle loads and environmental effects, the surface and internal cracks of the pavement expand and connect very quickly. Once the ultimate tensile strength of the concrete is reached, structural defects such as broken plates will occur.
[0003] Nowadays, prefabricated concrete pavements have been widely studied by scholars due to their advantages of fast construction and easy maintenance. At the same time, compared with ordinary concrete, high-strength and high-toughness concrete (ECC) exhibits strain hardening characteristics, ultra-high tensile ductility and excellent crack control ability in mechanical properties. Therefore, the use of high-strength and high-toughness concrete to prepare prefabricated concrete road panels has extremely broad application prospects. High-strength and high-toughness concrete (ECC) is formed by pouring cement, water, sand, fly ash, fiber, etc. Its water-cement ratio is usually between 0.3-0.35, does not contain coarse aggregate, and fiber materials with high elastic modulus (3.5-205GPa) and high tensile strength are added during pouring. However, compared with ordinary concrete, since ECC does not contain coarse aggregate in the mix ratio and uses a large amount of silicate cement, more energy is consumed during the preparation process of ECC, and more carbon dioxide and other harmful gases are produced, which does not conform to the current concept of preparing low-carbon green sustainable building materials. In addition, PVA fibers need to be added to ECC to achieve the bridging effect of the fibers and delay the extension of cracks when the concrete components are subjected to bending and tension. However, the cost of PVA fibers is relatively high, especially the price of Kuraray PVA fibers is as high as 200,000 yuan per ton, which leads to extremely high preparation costs of ECC and limits the application of ECC in actual engineering.
[0004] On the other hand, the concrete pavement in my country's coastal areas has long been in contact with a soft foundation rich in chloride ions, and the chloride ion content in the environment is higher and the penetration is stronger. Therefore, the concrete pavement in coastal areas is more susceptible to chloride ion erosion, causing internal steel bar modification and significantly reducing its service life.
[0005] Therefore, for the technical field of this invention, how to provide a prefabricated concrete pavement material with a new structure and a preparation method thereof to solve or improve at least one of the above-mentioned technical problems has a relatively practical significance. Summary of the invention
[0006] The object of the present invention is to provide a prefabricated concrete pavement material of a new structure and a preparation method thereof, so as to solve or improve at least one technical problem existing in the related art.
[0007] In order to solve the above technical problems, the technical solution proposed by the present invention is:
[0008] An assembled concrete pavement material is prepared from the following raw materials in parts by weight: 180-310 parts of cement, 105-320 parts of limestone calcined clay cement, 265-930 parts of fly ash, 50-250 parts of silica fume, 250 parts of quartz sand, 20-150 parts of water reducer, 10-20 parts of thickener, 5-15 parts of POM fiber, 5-15 parts of PP fiber, 5-15 parts of PVA fiber, and 115-500 parts of water.
[0009] As an improvement of the above-mentioned assembled concrete pavement material in one aspect, the POM fiber has a diameter of 200 μm, a length of 12 mm, an elastic modulus greater than 8 GPa, a breaking strength greater than 800 MPa, and a breaking elongation of 18%.
[0010] As an improvement on the above-mentioned prefabricated concrete pavement material, the PP fiber has a diameter of 18 μm, a length of 15 mm, an elastic modulus greater than 4 GPa, a breaking strength greater than 350 MPa, and an elongation at break of 20%.
[0011] As an improvement on the above-mentioned prefabricated concrete pavement material, the PVA fiber has a diameter of 39 μm, a length of 12 mm, an elastic modulus of about 40 GPa, a breaking strength greater than 1600 MPa, and a breaking elongation of 6%.
[0012] As an improvement on the above-mentioned prefabricated concrete pavement material, the 28-day compressive strength of cement is not less than 42.5 MPa, the flexural strength is not less than 6.5 MPa, the initial setting time is not less than 45 minutes, and the final setting time is not more than 600 minutes.
[0013] As an improvement on the above-mentioned prefabricated concrete pavement material, the fineness of the silica fume is 5000 mesh.
[0014] As an improvement on the above-mentioned prefabricated concrete pavement material, the fineness of the fly ash is 3000 mesh.
[0015] As an improvement on the above-mentioned prefabricated concrete pavement material, the silicon dioxide content of the fly ash is not less than 50%.
[0016] As an improvement on the above-mentioned prefabricated concrete pavement material, the water-cement ratio of the prefabricated concrete pavement material is 0.2 to 0.35.
[0017] The assembled concrete pavement material of the present invention partially replaces PVA fibers with POM fibers and PP fibers. On the one hand, the cost is reduced by changing the fiber types. On the other hand, the mixing effect of the three types of fibers is improved. At the same time, limestone calcined clay cement material is used instead of silicate cement material to prepare high-strength and high-toughness assembled concrete road panels, improve their resistance to chloride ion penetration, reduce their carbon content and cost, and thus be applied to coastal areas.
[0018] On the other hand, the present invention provides a method for preparing the above-mentioned prefabricated concrete pavement material, comprising the following steps: cement, limestone calcined clay cement, fly ash, silica fume, quartz sand and thickener are placed in a reactor and stirred for 3 minutes until uniform, then POM fiber, PP fiber, PVA fiber are added and stirred for 2 minutes, water and water reducer are added and stirred for 5 minutes to form a uniform mixture, and the mixed slurry is placed in a high humidity and normal temperature environment to solidify to obtain a high-strength and high-toughness concrete material.
[0019] As an improvement on one aspect of the preparation method of the above-mentioned prefabricated concrete pavement material, the following steps are included: after the prefabricated concrete road panel is prepared, an electric current is passed through both ends of the road panel by an electrochemical method, and the ions inside the concrete (such as calcium ions and hydroxide ions) move along the direction of the electric field to fill the pores and cracks in the concrete.
[0020] As an improvement in one aspect of the preparation method of the above-mentioned assembled concrete pavement material, after the assembled concrete road panel is prepared, an electric current is passed through both ends of the road panel by an electrochemical method, and the ions (such as calcium ions and hydroxide ions) inside the concrete move along the direction of the electric field to fill the pores and cracks in the concrete, including the following steps:
[0021] After the specimens were poured, they were cured for 28 days, and electrochemical technology was used to improve their resistance to chloride ion penetration:
[0022] (1) Preparation stage: Clean the surface of the prefabricated concrete road panel to ensure good contact of the electrodes. Install the electrodes on the concrete surface and add electrolyte (such as water or salt solution) between the electrodes and the concrete;
[0023] (2) Applying an electric field: applying direct current or alternating current through an external power source, with the current magnitude and duration adjusted according to specific needs;
[0024] (3) Monitoring and control: During the treatment process, the current, voltage and ion concentration changes are monitored in real time to ensure the effectiveness and safety of the treatment process;
[0025] (4) Post-treatment stage: After the electrochemical treatment is completed, the electrolyte and electrodes are cleaned and the concrete is subjected to necessary surface treatment (such as coating or maintenance) to ensure long-term effects.
[0026] Since the preparation method of the above-mentioned assembled concrete pavement material has the same inventive concept as the above-mentioned assembled concrete pavement material, the preparation method of the above-mentioned assembled concrete pavement material has all the technical effects of the above-mentioned assembled concrete pavement material, which will not be repeated here. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1 It is a schematic diagram of a method for preparing a prefabricated concrete pavement material according to one embodiment of the present invention.
[0029] Figure 2 It is a schematic diagram of a method for preparing a prefabricated concrete pavement material according to one embodiment of the present invention.
[0030] Figure 3 Schematic diagram of the electrochemical treatment step of the method for preparing the assembled concrete pavement material according to one embodiment of the present invention.
[0031] Figure 4 Schematic diagram of the electrochemical treatment step of the method for preparing the assembled concrete pavement material according to one embodiment of the present invention. DETAILED DESCRIPTION
[0032] In the description of the present invention, it is to be understood that the terms “center”, “longitudinal”, “lateral”, “up”, “down”, “front”, “back”, “left”, “right”, “vertical”, “horizontal”, “top”, “bottom”, “inside”, “outside”, “axial”, “radial”, etc., indicating orientations or positional relationships are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.
[0033] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is more than two, unless otherwise clearly and specifically defined.
[0034] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0035] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being "above", "above" or "above" a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being "below", "below" or "below" a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.
[0036] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0037] The prefabricated concrete pavement material provided in an embodiment of the present invention is prepared from the following raw materials in parts by weight: 180 to 310 parts of cement, 105 to 320 parts of limestone calcined clay cement, 265 to 930 parts of fly ash, 50 to 250 parts of silica fume, 250 parts of quartz sand, 20 to 150 parts of water reducer, 10 to 20 parts of thickener, 5 to 15 parts of POM fiber, 5 to 15 parts of PP fiber, 5 to 15 parts of PVA fiber, and 115 to 500 parts of water.
[0038] Among them, limestone calcined clay cement is a kind of cement composed of limestone, calcined clay, kaolin, gypsum and clinker, mainly including 50% cement, 30% kaolin, 15% limestone and 5% gypsum. Limestone and calcined clay can react to form carbon aluminate hydrate to promote cement hydration. POM fiber diameter is 200μm, length is 12mm, elastic modulus is greater than 8GPa, breaking strength is greater than 800MPa, and elongation at break is about 18%. PP fiber diameter is 18μm, length is 15mm, elastic modulus is greater than 4GPa, breaking strength is greater than 350MPa, and elongation at break is about 20%. PVA fiber diameter is 39μm, length is 12mm, elongation at break is about 6%, elastic modulus is about 40GPa, and breaking strength is greater than 1600MPa. The 28-day compressive strength of cement is not less than 42.5MPa, the flexural strength is not less than 6.5MPa, the initial setting time is not less than 45 minutes, the final setting time is not more than 600 minutes, and it has good stability. The fineness of silica fume is 5000 mesh, the fineness of fly ash is 3000 mesh, and the silicon dioxide content is not less than 50%. It should be noted that limestone calcined clay cement is composed of limestone, calcined clay, gypsum and clinker, and uses natural minerals and industrial by-products (secondary clay) as raw materials. Compared with silicate cement, it has lower carbon emissions and lower costs, thereby reducing the preparation cost of ECC. Therefore, limestone calcined clay cement partially replaces silicate cement, reducing the carbon emissions and preparation cost of ECC.
[0039] In some embodiments of the present invention, the water-to-cement ratio of the prefabricated concrete pavement material provided by the embodiments of the present invention is 0.2 to 0.35.
[0040] In the prefabricated concrete pavement material provided in the embodiment of the present invention, PVA fibers are partially replaced by POM fibers and PP fibers. This reduces costs by changing the fiber types, and improves the toughness of the concrete by the mixing effect of the three types of fibers. At the same time, limestone calcined clay cement materials are used instead of silicate cement materials to prepare high-strength and high-toughness prefabricated concrete road panels, improve their resistance to chloride ion penetration, and reduce their carbon content and cost, so that they can be applied in coastal areas.
[0041] like Figures 1 to 4As shown, the preparation method of the assembled concrete pavement material provided by the embodiment of the present invention comprises the following steps: cement, limestone calcined clay cement, fly ash, silica fume, quartz sand and thickener are placed in a reactor and stirred for 3 minutes until uniform, then POM fiber, PP fiber and PVA fiber are added and stirred for 2 minutes, and water and water reducing agent are added and stirred for 5 minutes to form a uniform mixture. The mixed slurry is placed in a high humidity and normal temperature environment and solidified to obtain a high-strength and high-toughness concrete material.
[0042] After the specimens were poured, they were cured for 28 days, and electrochemical technology was used to improve their resistance to chloride ion penetration: (1) Preparation stage: Clean the surface of the prefabricated concrete pavement panel to ensure good contact of the electrodes. Install the electrodes on the concrete surface and add an electrolyte (such as water or salt solution) between the electrodes and the concrete. (2) Apply an electric field: Apply direct current or alternating current through an external power supply, and the current size and time are adjusted according to specific needs. (3) Monitoring and control: During the treatment process, the changes in current, voltage and ion concentration are monitored in real time to ensure the effectiveness and safety of the treatment process. (4) Post-treatment stage: After the electrochemical treatment is completed, clean the electrolyte and electrodes, and perform necessary surface treatment (such as coating or maintenance) on the concrete to ensure long-term effects. Figure 4 As shown, after preparing high-strength and high-toughness concrete according to the above steps, copper sheets are connected to both ends of the assembled concrete road panel, and 24V direct current is passed. Under the action of the electric field, the ions inside the concrete (such as calcium ions and hydroxide ions) move along the direction of the electric field. This ion migration can fill the pores and cracks in the concrete and enhance its density. At the same time, the electric field promotes the chemical reaction of ions in the concrete to generate new solid products (such as calcium hydroxide and carbon dioxide react to generate calcium carbonate). These products can fill the pores, effectively preventing chloride ions from entering the concrete and corroding the steel bars, and enhancing the impermeability and chloride ion permeability of the concrete road panel.
[0043] In the method for preparing the assembled concrete pavement material provided in the embodiment of the present invention, Figures 1 to 4 As shown, the method comprises the following steps: mixing cement, calcined limestone clay, fly ash, silica fume, quartz sand and thickener in a reaction kettle for 3 minutes until uniform, then adding fiber material and mixing for 2 minutes, adding water and water reducing agent and mixing for 5 minutes to form a uniform mixture. After the mixed slurry is solidified in a high humidity and room temperature environment, a high-strength and high-toughness concrete material can be obtained. Figure 3 to Figure 4As shown, after the preparation of the assembled concrete road panel is completed, an electric current is passed through both ends of the road panel by an electrochemical method, and the ions inside the concrete (such as calcium ions and hydroxide ions) move along the direction of the electric field to fill the pores and cracks in the concrete, thereby improving the concrete road panel's resistance to chloride ion penetration. After the assembled concrete road panel is completed, an electric current is passed through both ends of the road panel by an electrochemical method, and the ions inside the concrete (such as calcium ions and hydroxide ions) move along the direction of the electric field to fill the pores and cracks in the concrete, including the following steps: After the test piece is cast, it is cured for 28 days, and the electrochemical technology is used to improve its resistance to chloride ion penetration: (1) Preparation stage: Clean the surface of the assembled concrete road panel to ensure good contact of the electrodes. Install electrodes on the concrete surface and add electrolyte (such as water or salt solution) between the electrodes and the concrete; (2) Apply electric field: apply direct current or alternating current through an external power supply, and the current size and time are adjusted according to specific needs; (3) Monitor and control: During the treatment process, monitor the changes in current, voltage and ion concentration in real time to ensure the effectiveness and safety of the treatment process; (4) Post-treatment stage: After the electrochemical treatment is completed, clean the electrolyte and electrodes, and perform necessary surface treatment (such as coating or maintenance) on the concrete to ensure long-term effects. On the one hand, the present invention partially replaces silicate cement with limestone calcined clay cement, thereby reducing the carbon emissions and preparation costs of ECC. On the other hand, the resistance of concrete road panels to chloride ion penetration is improved by replacing cement with limestone calcined clay and electrochemical methods. It should be noted that limestone calcined clay cement is composed of limestone, calcined clay, gypsum and clinker. It uses natural minerals and industrial by-products (secondary clay) as raw materials. Compared with silicate cement, it has lower carbon emissions and lower costs, thereby reducing the preparation cost of ECC. On the other hand, the calcined limestone provides additional nucleation sites for cement hydration, which improves the hydration degree of cement to a certain extent and enhances the binding ability of cement-based materials with chloride ions, thereby effectively improving the concrete's resistance to chloride ion penetration. Electrochemical method: The internal ions of concrete (such as calcium ions and hydroxide ions) move along the direction of the electric field. This ion migration can fill the pores and cracks in the concrete and enhance its density, thereby improving the resistance of the assembled road panels to chloride ion penetration.
[0044] In a specific embodiment 1 of the present invention, the preparation method of the prefabricated concrete pavement material provided in the embodiment of the present invention comprises the following steps: (1) weighing 270 parts of cement, 265 parts of fly ash, 150 parts of limestone calcined clay cement, 250 parts of silica fume, 250 parts of quartz sand, and 10 parts of thickener, stirring in a reactor for 3 minutes to obtain a dry mixture; (2) weighing 5 parts of POM fiber, 15 parts of PP fiber, and 15 parts of PVA fiber, putting them into the dry mixture and stirring for 2 minutes until uniform; (3) slowly adding 20 parts of water reducer and 115 parts of water, stirring for 5 minutes, obtaining a uniform mixture, and loading it into a road panel mold and curing for 28 days to form it.
[0045] In specific embodiment 2 of the present invention, the preparation method of the prefabricated concrete pavement material provided in the embodiment of the present invention comprises the following steps: (1) weighing 200 parts of cement, 265 parts of fly ash, 320 parts of limestone calcined clay cement, 250 parts of silica fume, 250 parts of quartz sand, and 10 parts of thickener, stirring in a reactor for 3 minutes to obtain a dry mixture; (2) weighing 5 parts of POM fiber, 15 parts of PP fiber, and 15 parts of PVA fiber, putting them into the dry mixture and stirring for 2 minutes until uniform; (3) slowly adding 20 parts of water reducer to 115 parts of water, stirring for 5 minutes, obtaining a uniform mixture, and loading it into a road panel mold and curing for 28 days to form it.
[0046] In specific embodiment 3 of the present invention, the preparation method of the prefabricated concrete pavement material provided in the embodiment of the present invention comprises the following steps: (1) weighing 180 parts of cement, 265 parts of fly ash, 300 parts of limestone calcined clay cement, 250 parts of silica fume, 250 parts of quartz sand, and 10 parts of thickener, stirring in a reactor for 3 minutes to obtain a dry mixture; (2) weighing 15 parts of POM fiber, 15 parts of PP fiber, and 5 parts of PVA fiber, putting them into the dry mixture and stirring for 2 minutes until uniform; (3) slowly adding 20 parts of water reducer to 115 parts of water, stirring for 5 minutes, obtaining a uniform mixture, and loading it into a road panel mold and curing for 28 days to form it.
[0047] In specific embodiment 4 (control example) of the present invention, the preparation method of concrete pavement material comprises the following steps: (1) weighing 480 parts of cement, 265 parts of fly ash, 250 parts of silica fume, 250 parts of quartz sand and 10 parts of thickener, stirring in a reactor for 3 minutes to obtain a dry mixture; (2) weighing 15 parts of POM fiber, 15 parts of PP fiber and 5 parts of PVA fiber, putting them into the dry mixture and stirring for 2 minutes until uniform; (3) slowly adding 20 parts of water reducer into 115 parts of water, stirring for 5 minutes to obtain a uniform mixture, and putting it into a road panel mold for curing for 28 days to form it.
[0048] The cement-based mixture materials prepared in Examples 1 to 4 were poured into a mold, demolded after curing at room temperature for 1 day, and placed in a high humidity and room temperature environment for curing for 27 days. The compressive strength, tensile strength and 24h electrical flux were then tested. The test results are shown in Table 1.
[0049]
[0050] As can be seen from the table, the ultimate strain of high-strength and high-toughness concrete prepared in Examples 1 to 3 is not less than 3%. At the same time, the compressive strength is not less than 60MPa, and the 24h electric flux is below 1600C. In addition, compared with Example 4, with the addition of limestone calcined clay cement, the 24h electric flux of concrete is greatly reduced, and it decreases with the increase in the dosage of limestone calcined clay cement, which shows that limestone calcined clay cement can play a good role in improving the resistance to chloride ion permeability. Thus, limestone calcined clay cement replaces silicate cement and also plays a good hardening and condensation effect. At the same time, the mixing of POM fiber, PP fiber, and PVA fiber can play a mixed effect. When concrete is subjected to tension, the extension of its crack width is limited, and its toughness is effectively improved. At the same time, limestone calcined clay cement contains a large amount of volcanic ash components, which play an activation role and a nucleation site role, promote the hydration process of cement, effectively improve the compactness of concrete, enhance the compressive strength, and effectively improve the resistance to chloride ion penetration.
[0051] Electrochemical treatment example:
[0052] First, cast and form the assembled concrete road panel according to the mix ratio of Example 3, control different power-on times, and then cut the concrete road panel into the test block size required by the electric flux test. The specific embodiment is as follows:
[0053] Embodiment 5:
[0054] The control power-on voltage is 24V and the power-on time is 6h.
[0055] Embodiment 6:
[0056] The control power-on voltage is 24V and the power-on time is 12h.
[0057] Embodiment 7:
[0058] The control power-on voltage is 24V and the power-on time is 24h.
[0059] Embodiment 8 (control group):
[0060] Without electrochemical treatment.
[0061] Test items 24h electrical flux (C) Example 5 1371 Example 6 1354 Example 7 1291 Example 8 1392
[0062] As can be seen from the above table, compared with Example 8 without electrochemical treatment, the electric flux of the concrete road panel after electrochemical treatment is effectively reduced, which shows that electrochemical treatment can effectively improve the resistance of assembled concrete pavement materials to chloride ion penetration. In addition, as the power-on time increases, the electric flux decreases, indicating that the resistance of concrete pavement materials to chloride ion penetration increases with the increase of electrochemical treatment time. Therefore, electrochemical treatment can improve the resistance of assembled concrete pavement materials to chloride ion penetration. As described above, a kind of assembled concrete pavement material suitable for strong corrosion and weak foundation conditions in coastal areas is prepared.
[0063] In summary, the prefabricated concrete pavement material of the present invention partially replaces PVA fiber with POM fiber and PP fiber, so that on the one hand, the cost is reduced by changing the fiber type, and on the other hand, the hybrid effect of the three types of fiber blending improves the toughness of concrete. At the same time, limestone calcined clay cement material is used to replace silicate cement material, thereby preparing high-strength and high-toughness prefabricated concrete road panels, improving their resistance to chloride ion penetration, reducing their carbon content and cost, and applying them to coastal areas. It can be seen that the prefabricated concrete pavement material of the present invention has the following technical effects: by replacing silicate cement with limestone calcined clay cement, the ECC preparation cost is reduced, and the resistance to chloride ion penetration of concrete is improved. The cost is reduced by changing the fiber type, and the hybrid effect of the three types of fiber blending improves the toughness of concrete. An electrochemical method is used to improve the resistance to chloride ion penetration of concrete road panels.
[0064] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0065] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. An assembled concrete pavement material, characterized in that: The invention is prepared from the following raw materials in parts by weight: 180-310 parts of cement, 105-320 parts of limestone calcined clay cement, 265-930 parts of fly ash, 50-250 parts of silica fume, 250 parts of quartz sand, 20-150 parts of water reducer, 10-20 parts of thickener, 5-15 parts of POM fiber, 5-15 parts of PP fiber, 5-15 parts of PVA fiber and 115-500 parts of water.
2. The assembled concrete pavement material according to claim 1, characterized in that: The POM fiber has a diameter of 200 μm, a length of 12 mm, an elastic modulus greater than 8 GPa, a breaking strength greater than 800 MPa, and a breaking elongation of 18%.
3. The assembled concrete pavement material according to claim 1, characterized in that: The PP fiber has a diameter of 18 μm, a length of 15 mm, an elastic modulus greater than 4 GPa, a breaking strength greater than 350 MPa, and an elongation at break of 20%.
4. The assembled concrete pavement material according to claim 1, characterized in that: The PVA fiber has a diameter of 39 μm, a length of 12 mm, an elastic modulus of about 40 GPa, a breaking strength greater than 1600 MPa, and a breaking elongation of 6%.
5. The assembled concrete pavement material according to claim 1, characterized in that: The 28-day compressive strength of cement shall not be less than 42.5MPa, the flexural strength shall not be less than 6.5MPa, the initial setting time shall not be less than 45 minutes, and the final setting time shall not exceed 600 minutes.
6. The assembled concrete pavement material according to claim 1, characterized in that: The fineness of silica fume is 5000 mesh.
7. The assembled concrete pavement material according to any one of claims 1 to 6, characterized in that: The fineness of the fly ash is 3000 meshes, the silicon dioxide content of the fly ash is not less than 50%, and the water-binder ratio of the assembled concrete pavement material is 0.2-0.
35.
8. A method for preparing an assembled concrete pavement material according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: mixing cement, limestone calcined clay cement, fly ash, silica fume, quartz sand and thickener in a reaction kettle for 3 minutes until the mixture is uniform, then adding POM fiber, PP fiber and PVA fiber and mixing for 2 minutes, adding water and a water reducing agent and mixing for 5 minutes to form a uniform mixture, and the mixed slurry is placed in a high humidity and normal temperature environment for coagulation to obtain a high-strength and high-toughness concrete material.
9. The method for preparing the assembled concrete pavement material according to claim 8, characterized in that: The method comprises the following steps: after the fabricated concrete road panel is prepared, current is passed through both ends of the road panel by an electrochemical method, and ions inside the concrete move along the direction of the electric field to fill the pores and cracks in the concrete.
10. The method for preparing the assembled concrete pavement material according to claim 9, characterized in that: After the fabricated concrete road panel is prepared, an electric current is passed through both ends of the road panel by an electrochemical method, and the ions inside the concrete move along the direction of the electric field to fill the pores and cracks in the concrete, including the following steps: After the specimens were poured, they were cured for 28 days, and electrochemical technology was used to improve their resistance to chloride ion penetration: (1) Preparation stage: Clean the surface of the assembled concrete road slab to ensure good contact of the electrodes. Install the electrodes on the concrete surface and add electrolyte between the electrodes and the concrete; (2) Applying an electric field: applying direct current or alternating current through an external power source, with the current magnitude and duration adjusted according to specific needs; (3) Monitoring and control: During the treatment process, the current, voltage and ion concentration changes are monitored in real time to ensure the effectiveness and safety of the treatment process; (4) Post-treatment stage: After the electrochemical treatment is completed, the electrolyte and electrodes are cleaned and the concrete is subjected to necessary surface treatment to ensure long-term effects.